Social Media Trends on Generation Z's Lifestyle - Ilahana, Anjani Dzikry; Tsabitah, Najah; Fadhillah, Intan (Universitas Negeri Semarang, 2024)
This study examines the impact of social media trends on Generation Z's lifestyle, focusing on their physical and mental health. Generation Z, born between 1997 and 2012, is profoundly influenced by digital platforms like Instagram, TikTok, and YouTube. The research uses qualitative content analysis to explore how social media shapes their behavior, emphasizing the prevalence of unhealthy habits such as poor diet, lack of physical activity, and the mental stress of striving for social acceptance. The findings indicate that social media trends often promote rapid and detrimental lifestyle changes, leading to physical issues like obesity and mental health problems such as anxiety and depression. The study highlights the importance of educating Generation Z on balanced media use and healthier lifestyle choices. Recommendations for future research include exploring effective interventions to mitigate these negative influences and implementing comprehensive educational programs. A multi-faceted approach involving parents, schools, and policymakers is essential to guide Generation Z towards healthier habits.